EFFECTIVENESS OF KARAMUNTING FLOWER EXTRACT (Melastoma malabathricum L) ON THE STREPTOCOCCUS MUTANS GLUCOSYLTRANSFERASE ENZYME ACTIVITY - Muhammad Zainal Fikri; Deby Kania Tri Putri; Muhammad Yanuar Ichrom Nahzi (FKG Unlam, 2019)
Background: Caries is a chronic disease of mineral ions continuous loss caused by bacteria in oral cavity. One of the main bacteria is Streptococcus mutans. This bacterium is able to synthesize the glucosyltransferase enzyme (GTF), which function is to catalyze polysaccharides in the form of sucrose into sticky glucans. This pathogenic property also has function in helping bacteria to stick and accumulate on the tooth surface, so it can increase the occurrence of the demineralization process and dental caries. Karamunting flower extract, as a natural ingredient, has antibacterial property. This property is caused by the content of phenol, flavonoid and tannin, which can reduce the GTF S. mutans enzyme activity. Objectives: This study aimed to analyze the effectiveness of karamunting flower extract (Melastoma malabathricum L) on the activity of the Stretococcus mutans glucosyltransferase enzyme. Methods: This study used a post-test only with control group design with karamunting flower extract samples in various concentration, including 40%, 50%, 60%, 70%, measuring enzyme activity with 4 repetitions in each group. Results: The data were analyzed using One Way ANOVA, which got p = 0,000 (p <0.05) and followed by Post Hoc LSD test that showed significant difference between each group (p <0.05). Data showed that concentrations of 40%, 50%, 60%, and 70% can reduce GTF S. mutans enzyme activity. Conclusion: Karamunting flower extract has the effectiveness of reducing the GTF enzyme activity of S. mutans.